Longitudinal colonisation by Streptococcus pneumoniae and nasopharyngeal microbial interactions in health and disease: a South African birth cohort study - Dube, Felix Sizwe (Division of Medical Biochemistry, 2016)
Streptococcus pneumoniae (the pneumococcus) is the most common cause of childhood pneumonia. Nasopharyngeal (NP) colonization by the pneumococcus is a necessary first step in the pathogenesis of pneumonia and yet the dynamic nature of pneumococcal colonization remains incompletely understood. In children, asymptomatic colonization of the nasopharynx by the pneumococcus is common and also serves as a reservoir for person-to-person transmission. We aimed to investigate in detail, the dynamics of pneumococcal nasopharyngeal carriage over the first year of life, in a cohort of South African children, particularly after implementation of the 13-valent pneumococcal conjugate vaccine (PCV-13). The study will further elucidate the interaction of S. pneumoniae with other respiratory pathogens and how such interactions may contribute development of severe disease.